PELAKSANAAN PENEMPATAN PEKERJA MIGRAN INDONESIA DI MALAYSIA BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2017 TENTANG PELINDUNGAN PEKERJA MIGRAN INDONESIA - Darwati (Fakultas Hukum Universitas Borobudur, 2022)
Placement of Indonesian Migrant Workers is an effort to realize equal rights and opportunities for workers to obtain decent work and income. Placement of Indonesian Migrant Workers has been regulated in Law Number 18 of 2017 concerning Protection of Indonesian Migrant Workers. However, the placement of Indonesian Migrant Workers abroad still creates many problems, for example, complicated bureaucratic procedures, many fees outside the placement system, lack of official documents, and difficulty accessing communications with the Indonesian Embassy. Therefore, there are two issues that will be discussed in this article, namely how to implement the placement of Indonesian Migrant Workers in Malaysia and what are the obstacles in implementing the placement of Indonesian Migrant Workers in Malaysia. The research method used is normative juridical and sociological juridical. The result of the research is that the implementation of the placement of Indonesian Migrant Workers in Malaysia by P3MI goes through three stages, namely pre-placement, placement and post-placement. These three stages are in accordance with the provisions of Article 7 of Law Number 18 of 2017 concerning Protection of Indonesian Migrant Workers jo. Article 6 to Article 27 of the Minister of Manpower Regulation Number 9 of 2019 concerning Procedures for Placement of Indonesian Migrant Workers. Obstacles in implementing the placement of Indonesian Migrant Workers in Malaysia include convoluted bureaucratic and administrative problems that hinder, lack of coordination between agencies, weak human resources, many P3MIs who are not licensed or whose operating permits are no longer active or have expired, and the large number of levies outside the placement system.